Disruptive Innovations, Fundamental Strength and Stock Winners: Implications for Stock Index Revisions. Issue 3 (September 2020) - Agrawal, Tarunika Jain; Sehgal, Sanjay; Agrawal, Rahul
Globally, disruptions driven by technological advancements are visible in the form of unicorns and declining lifespan of the index constituents. Sectors such as information technology, financial services, energy, consumer goods and automobile are found to be more prone to disruptive innovation. Assessing the financial strength of the incumbents is crucial to assess their strength to endure disruption. We construct a fundamental strength index (FSI) using 11 financial performance measures covering 7 key attributes, namely profitability, efficiency, solvency, liquidity, net investments, pursuance of innovation and entry barriers, over the 5-year period 2014–2019. FSI helps in categorizing stocks of National Stock Exchange (NSE) 200 universe as 'A' being the fundamentally strongest and 'C' being the weakest. Potential crossovers can take place between 'C' category stock in Nifty 50 (Next 50) and 'A' category stock belonging to the Next 50 (Nifty Midcap 100). The results show that the disruptor's portfolio (Next 50 stocks) outperforms the incumbent's portfolio (Nifty 50 constituents) with a return of 1.61 per cent vs 0.47 per cent. A similar observation holds true for the Next 50 and Nifty Midcap 100, with the disruptor's portfolio surpassing the incumbent's portfolio (return of 2.59% vs 0.44%). The study has significant implications for the policymakers, investors, companies and academicians.